Building Responsible Character in Students Through the Implementation of the Seven Habits of Highly Effective Indonesian Children Program in Elementary Schools - Adhimas Wahyu Nur Karim; Achmad Fathoni (Journal of Educational Sciences, 2026)
This study aims to describe the implementation of the Seven Habits of Great Indonesian Children Program as an effort to build responsible character in elementary school students. This program is part of character education, oriented towards forming positive habits through instilling the values of discipline, hard work, independence, and responsibility in daily life at school. This study used a qualitative approach with descriptive methods. The research subjects included teachers, students, and parents at a public elementary school that has implemented the program. Data were collected through interviews, observation, and documentation and analyzed using data reduction, data presentation, and conclusion-drawing techniques. The results of this study show significant changes, particularly in children's responsible behavior, both at school and at home. The school also established good cooperation and communication with parents so that the Seven Habits of Great Indonesian Children Program, especially regarding the character of responsibility, could run smoothly and experience improvement. It can be concluded that the Seven Habits of Great Indonesian Children Program has a positive impact on children's character development.